Initial File-Placement In Data Grid Environment Using Game Theory And Fictitious Play - Indrayanto, Aloysius (2008)
Data allocation comprises data placement or migration. It is one of the main considerations in the design of a distributed data sharing system. Peruntukan data merangkumi peletakan atau migrasi data. Ini merupakan salah satu pertimbangan utama dalam reka bentuk sistem perkongsian data teragih.